Front Street, Dawson, Yukon Territory, July 1899. - Hegg, Eric A., 1867-1948 (1899)
Shows crowded street scene with advertising banners strung across the street. Caption on image: "Street scene Dawson July 99" Original photograph by Eric A. Hegg 2333; copied by Larss and Duclos No. 16 appears in the lower left corner. See Hegg 431 for similar view. Klondike Gold Rush.